2021
DOI: 10.3390/molecules26133907
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea and Its Relation to Human Gut Microbiome

Abstract: Green tea can influence the gut microbiota by either stimulating the growth of specific species or by hindering the development of detrimental ones. At the same time, gut bacteria can metabolize green tea compounds and produce smaller bioactive molecules. Accordingly, green tea benefits could be due to beneficial bacteria or to microbial bioactive metabolites. Therefore, the gut microbiota is likely to act as middle man for, at least, some of the green tea benefits on health. Many health promoting effects of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 85 publications
(168 reference statements)
0
24
0
Order By: Relevance
“…184 Furthermore, green tea consumption, because of its content of polyphenolic compounds, is linked with positive impacts on the microbiome (see also section H 2 S Metabolism and Signaling Pathways ). 185…”
Section: Dysbiosis and Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…184 Furthermore, green tea consumption, because of its content of polyphenolic compounds, is linked with positive impacts on the microbiome (see also section H 2 S Metabolism and Signaling Pathways ). 185…”
Section: Dysbiosis and Cardiovascular Diseasesmentioning
confidence: 99%
“…184 Furthermore, green tea consumption, because of its content of polyphenolic compounds, is linked with positive impacts on the microbiome (see also section H 2 S Metabolism and Signaling Pathways). 185 Exercise along with diet interventions can have significant impact on the microbiota. After such intervention for 6 weeks, the Firmicutes/Bacteroidetes ratio displayed a marked increase which was found to reduce the resting heart rate without changing systolic or diastolic blood pressure in adolescents with obesity.…”
Section: Impact Of Diet and Physical Activitymentioning
confidence: 99%
“…As autoimmune disorders are closely related to inflammation (studies emphasize the role of T cells as the primary factors connecting inflammation and autoimmune pathology) [169], it can be assumed that as inflammation markers are lowered due to the consumption of tea or polyphenols isolated therefrom, the organism's immune sensitivity is also decreased. It has been demonstrated that green tea can correct microbial dysbiosis, influencing the growth of bacteria contributing to inflammatory states by facilitating the development of beneficial bacteria, inhibiting the growth of harmful ones, or increasing the production of desirable metabolites such as short-chain fatty acids [170]. Short-chain fatty acids show anti-inflammatory and immunomodulatory properties [171].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…TP increases the diversity of the intestinal microbiota, improves the number of beneficial microflora and inhibits some pathogenic strains. This interaction between TP and the intestinal microbiota contributes to the relief and alleviation of intestinal-related diseases [ 11 , 12 , 13 ]. TP can also be decomposed into different metabolites by microflora in the colon, many of which have higher anti-inflammatory activity and bioavailability than their precursors [ 11 , 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%